2021
DOI: 10.1038/s41388-020-01594-4
|View full text |Cite
|
Sign up to set email alerts
|

C1GALT1 high expression is associated with poor survival of patients with pancreatic ductal adenocarcinoma and promotes cell invasiveness through integrin αv

Abstract: Pancreatic adenocarcinoma (PDAC) is a leading cause of cancer-related death. Altered glycosylation contributes to tumor progression and chemoresistance in many cancers. C1GALT1 is the key enzyme controlling the elongation of GalNAc-type O-glycosylation. Here we showed that C1GALT1 was overexpressed in 85% (107/126) of PDAC tumors compared with adjacent non-tumor tissues. High expression of C1GALT1 was associated with poor disease-free and overall survival (n = 99). C1GALT1 knockdown using siRNA suppressed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…In addition, overexpression or knockdown of C1GALT1 could facilitate or suppress tumor growth in vivo . It has been reported that C1GALT1 is essential for processes such as cell proliferation, migration, and invasion in a variety of malignancies ( Lee et al, 2020 ; Kuo et al, 2021 ). Our findings are consistent with previous reports, suggesting a pro-oncogenic role for C1GALT1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, overexpression or knockdown of C1GALT1 could facilitate or suppress tumor growth in vivo . It has been reported that C1GALT1 is essential for processes such as cell proliferation, migration, and invasion in a variety of malignancies ( Lee et al, 2020 ; Kuo et al, 2021 ). Our findings are consistent with previous reports, suggesting a pro-oncogenic role for C1GALT1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, RAC1 was a downstream effector of C1GALT1 in LUAD. Previous studies have mainly focused on the relationship between C1GALT1 and glycoproteins ( Lee et al, 2020 ; Kuo et al, 2021 ). Besides its direct function of producing aberrant glycoproteins, our current study provided new insights into the regulatory network of C1GALT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, impaired O-glycosylation and in particular, the extension of the (sialyl)Tnantigen to (sialyl)-T-antigen of the TRAIL death receptor was found to alter receptor oligomerization state and to confer apoptosis resistance to the cells [54]. Overexpression of C1GALT1, a key enzyme controlling the elongation of the Tn-antigen to T-antigen in turn was also found to enhance migration, invasion, tumour growth, and metastasis of pancreatic cancer cells [58]. In line with these observations, our lectin microarray analyses showed that the levels of these truncated O-glycan glycotopes were much lower in non-invasive AE2 knockdown cells than in invasive (SW-48 Scr) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Heterologous expression of human enzymes that can biosynthesize CA-19-9 in a mouse model increased pancreatic inflammation, pointing to a potential role of this epitope in disease initiation (4). Pancreatic cell culture models have also shown a potential role for glycosylation in cell stemness, invasiveness and drug resistance (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%